Analysis of the state of the structure of a bus stop subjected to loads exerted by a green roof, case study: Bogotá, Colombia - Contreras, O.; Nuñez, F. (Revista Ingeniería de Construcción, 2020)
This article presents the analysis of the structural conditions of four modified bus stops with the change of a load represented by a green roof in the city of Bogotá. The methodology has two phases for accounting the bus stop behavior; As a first step, a finite element model was the main tool to compare the critical stresses of the structure before and after the use of the green roof, and to observe the location of said stressed areas before the happening of a seismic force; and on the other hand a physical model which is subjected to different frequencies in a shaking table to compare the movement and damage of the structure before and after being modified. An increase in stresses of about 80.57% took place by the connection between the column and the central beam, however, given that this value is less than the yield limit of the material, it can be said that the structure will not suffer damage due to the green roof additional load.